KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA MAN KOTA BAKTI KABUPATEN PIDIE - Zainal Abidin; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
AbstractLeadership is the ability to actuate and direct people to the goal of the school through various systematic stages, and it is the key to support the improvement of teachers’ professional competence in learning activities. This research aimed to find out the composing of the principal’s programing improving  the teachers’ professional competence, principal’s technique in improving the teachers’ professional competence, and the obstacles faced by the principal in improving the teachers’ professional competence in State Islamic Senior High School of Kota Bakti. This study used a qualitative approach with descriptive method. The techniques for the data collection were observation, interview, and documentation study. The data analysis procedures were data reduction, data display and data verification. The subjects in this study were the principal, vice principal and teachers. The results of this study were: (1) The program compilation of the headmaster was carried out by the principal with vice principal and teachers. The headmaster’s program in improving the professional competence of teachers was in the forms of: realizing the vision and mission of the school, complementing means and infrastructure, conducting activities for teacher development through seminars, continuing education and complementing means and facilities, and holding supervision for both teaching and administration; (2) The Headmaster’s technique for improving the professional competence of the teachers in State Islamic Senior High School of Kota Bakti was to guide, motivate teachers to do best in learning process, foster mental and quality of professionalism, make the climate of the school conducive, increase the motivation of teachers, and give reward and punishment; and (3) the obstacles faced by the headmaster were: less-motivated and careless teachers, the inclination of teachers that was very heterogeneous, either because of the position, age or because of education, lack of teachers’ awareness to their own learning device, teachers that did not have complete device, even it was just impressed sober, and the lack of utilization of internet media  as teachers’ reference in teaching.Keywords: leadership, principal/headmaster, professional competence, and teacher